Pelatihan Public Speaking untuk Meningkatkan Keterampilan dalam Berorganisasi di Sekolah Menengah Atas - Purwanti, Angel; Dompak, Timbul; Abidin, Sholihul; Wong, Angeline; Gea, Ras Gustini; Simatupang, Indri Anggi (PUAN INDONESIA, 2024)
Communication is one of the skills needed to speak, listen, overcome verbal communication barriers, understand other people's nonverbal communication, and develop ways to resolve conflicts. Public speaking and presentations are one types of communication skills. Public speaking and presentations are the process of conveying an oral message to an audience and are important activities in a culture where people have the right to speak freely. Speaking in public is not easy for him because many people are afraid of talking to new people, whether in class or public. Both presentation and public speaking abilities are necessary for students to succeed in the workplace when they are hired. To prepare students to speak and present in public as soon as possible, schools must provide public speaking and presentation training. This program was conducted at SMAK Immanuel Batam, a class X science and social science OSIS member. This exercise uses training as a means of carrying out community service. Mentoring or lectures, conversations, and practice are all part of the training that covers public speaking techniques and developing presenting concepts. These exercises help participants learn how to manage their nervousness and fear when giving public speeches and how to develop effective presenting ideas. The students enjoyed this activity which lasted for 5 days.